Towards a better future for biodiversity and people: Modelling Nature Futures - Kim, HyeJin; Peterson, Garry D.; Cheung, William W.L.; Ferrier, Simon; Alkemade, Rob; Arneth, Almut; Kuiper, Jan J.; Okayasu, Sana; Pereira, Laura; Acosta, Lilibeth A.; Chaplin-Kramer, Rebecca; den Belder, Eefje; et al. (Global environmental change, 2023)
[Display omitted] •Nature Futures Framework is a heiristic tool for creating positive futures for nature and people.•Nature Futures scenarios explore a mix of policies that progresses the world towards positive futures.•Reflecting diverse values and worldviews helps identify context-relevant interventions.•Mutually reinforcing positive social-ecological feedbacks can accelerate transformation pathways.•Indicators representing diverse values of nature build comprehensive evidence bases for policy. The Nature Futures Framework (NFF) is a heuristic tool for co-creating positive futures for nature and people. It seeks to open up a diversity of futures through mainly three value perspectives on nature – Nature for Nature, Nature for Society, and Nature as Culture. This paper describes how the NFF can be applied in modelling to support decision-making. First, we describe key considerations for the NFF in developing qualitative and quantitative scenarios: i) multiple value perspectives on nature as a state space where pathways improving nature toward a frontier can be represented, ii) mutually reinforcing key feedbacks of social-ecological systems that are important for nature conservation and human wellbeing, iii) indicators of multiple knowledge systems describing the evolution of complex social-ecological dynamics. We then present three approaches to modelling Nature Futures scenarios in the review, screening, and design phases of policy processes. This paper seeks to facilitate the integration of relational values of nature in models and strengthen modelled linkages across biodiversity, nature’s contributions to people, and quality of life.